Implementing task-based learning to improve ESL learners speaking skills in a primary DLP science classroom - Nur Farhana Taufik (2021)
This study aimed to investigate the implementation of the task-based learning approach(TBL) in improving ESL students speaking skills in a primary Dual Language Programme(DLP) Science classroom. This study also intended to obtain the DLP Science teachersviews regarding the implementation of the task-based learning approach for teaching Sciencein the English language. The mixed-methods approach combining the quasi-experimental design andsemi-structured interview was used. 65 Year Three students from two schools in Kuala Lumpur werechosen using the purposive sampling method. 35 participants from one school were chosen as theexperimental group, and 30 participants from another school were chosen as the controlgroup. Two Science teachers and two English teachers teaching in the DLP programmes in the twoschools also participated in the study. Three methods were employed to collect the datawhich were the pre- and post-test, classroom observation, and semi-structured interview.Quantitative data were analyzed using descriptive analysis, while the qualitative datawere analyzed using thematic analysis. The findings showed a significant difference inthe speaking test scores between the experimental group (M = 20.31, SD = 4.44) and the controlgroup (M = 16.30, SD = 4.11). The results also showed an increment in the number of studentsresponses and utterances in the experimental group over the course of the treatmentperiod. The experimental group teacher also perceived the TBL approach as helpful to students inbecoming more confident to speak in the classroom. In conclusion, the TBL approach has an effect inimproving the students speaking skills in the DLP Science classroom. This approach has thepotential as a viable teaching approach for the teaching of content subjects in theEnglish language in schools implementing the DLPprogramme.